Islamic Integrated Information Communication Technology Mathematics Learning Model for Students' Creativity and Environmental Awareness - Abdillah, Abdillah; Mastuti, Ajeng Gelora; Rijal, Muhammad; Sehuwaky, Nurlaila (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Mathematics teachers in integrated Islamic schools in Maluku are having problems implementing the integration of Islam into mathematics learning. This study aims to develop a learning model based on Islamic Integrated Information Communication Technology (IICT) to help teachers increase creativity in mathematical problem solving and students' environmental awareness. The main output of this research is an ICT-based active learning model that integrates Islamic sciences into mathematics learning to support the development of creativity skills in solving mathematical problems and students' environmental awareness at an early age. The development of the learning model in this study is a combination of the Plomp (2013), Dick & Carey (2015), and Joyce et al. (2009). Plomp's model was used for the research and model development phase, Dick & Carey for instructional design, and Joyce et al. for the model's contents. The resulting model is an adaptation of the hierarchical and procedural combination of the three developments. The research subjects are mathematics teachers and students. The data analysis technique used is the analysis of the instrument's validity, the IICT model, the practicality, and the effectiveness of the IICT model. Based on expert validation and testing results, the resulting model meets the needs of mathematics teachers and students of SMP/MTs in an integrated Islamic school environment. The results showed that the IICT learning model was qualified to help teachers integrate Islam in mathematics learning, increase creativity in solving math problems, and students' environmental awareness.